A Comparative Study of The Effect of Red Laser Wavelength and Green Laser Wavelength on The Healing of Achilles Tendon Injury In Rabbits - Ibrahim MH Alrashid (Kufa Journal for Veterinary Medical Sciences, 2015)
This study was designed to compare the effect of laser wavelength treatment on an  injured Achilles tendon; between two laser types red laser(650nm-10w) and green laser(532nm-10w). 18 rabbits, male and mature were used in the present study, the animals were divided into three groups, a control group, red laser group and green laser group. Each group was  tenoctomized the Achilles tendon, two groups were treated with one joule red laser and one joule green laser for 10 minutes daily for 14 days, laser beam applied vertically on the tendon dorsally, while the control group leaves to conventional recovery. The red laser group was showing  significant values at P≤0.05 in most items or parameters while green laser group was showed convergence with a control group except few items at P≤0.05, as well as a red laser group show better healing sonographically while histopathologically , images reveal no different in all groups at microscopic observation. In conclusions: laser therapy mainly depends on wavelength more thandensity and red laser better than green laser in treatment of Achilles tendon injury.